The Mini-Cross Prefenestration for Endovascular Repair of Aortic Arch Pathologies - Pei, Yifei; Zhu, Hongqiao; Xiao, Yu; Zhou, Jian; Jing, Zaiping (Frontiers in Cardiovascular Medicine, 2022)
Objective: To examine the feasibility, integrity, efficacy, and safety of endovascular repair of the aortic arch pathologies with the mini-cross prefenestration (MCPF) on stent grafts. Methods: First, to prove the feasibility of the MCPF, an in-vitro prefenestration experiment was conducted. Second, to examine the integrity of the MCPF stent grafts, a fatigue test was conducted. Then, the membranes and metal structures of stent grafts were examined by light microscopy and scanning electron microscopy (SEM). Third, a clinical experiment was conducted to investigate the efficacy and safety of this novel technique (ClinicalTrials.gov Identifier: NCT04544579). Results: All the 12 branch stents were successfully implanted and flared in vitro. After the fatigue test stimulating a 5-year cardiac cycle, no obvious disintegration or fracture was found in light microscopy or SEM. From December 2017 to February 2020, 26 patients with left subclavian arteries and/or left common carotid arteries involved received the novel technique. The endovascular repair with the MCPF was successfully performed on all the 26 (100%) patients. Eighteen (69.2%) patients underwent the reconstruction of the left subclavian artery (LSCA) only. The fenestrations of both the LSCA and left common carotid artery (LCCA) were conducted in 8 (30.8%) patients. Median operative time was 120 [interquartile range (IQR), 95–137.5] min and median revascularization time of the LSCA and LCCA was 30.5 (IQR, 22.8–42.0) s and 20.0 (IQR, 18.0–32.0) s separately. During the median follow-up duration of 38.9 (range, 18.8–44.2) months, one case needed an open surgery because of retrograde type A aortic dissection 3 months after implantation and no other complications or mortality occurred. The maximum aortic diameters were significantly decreased in patients with thoracic aortic dissection and thoracic aortic aneurysm (p < 0.05). Conclusion: The existing evidence demonstrated the safety, rapid branch artery revascularization, and positive aortic remodeling of the novel technique. Long-term observation is warranted to prove the durability.